PERAN MEDIA SOSIAL TERHADAP PERILAKU PEMILIH PEMULA PADA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA MANADO 2016 - Haloho, Elise E; Rembang, Max; Waleleng, Grace (ACTA DIURNA KOMUNIKASI, 2016)
Social media is one of communication channels are used during this period. Technological developments also facilitate the used of this channels. Social media now are used in many areas, health, economic, social, and political too. Manado is athriving town which is also using media as a channel of political communication at the election of mayor and deputy mayor of Manado 2016 . Pair of candidates for mayor and deputy mayor of Manado 2016 give a poltical message through social media with expectation get support and sympathy . Young voters are part of society that has greater tendency to accept the political message. Methode: This study use quatitative descriptive research methods and use New media teory and Stimulus organism respon. Result : Young voters is actively use social media and using social media as the main source of information. Pairs of candidate Harley Mangindaan and Jimmy Asiku was most active candidate who provide a political message through social media. Pairs of candidate Harley Mangindaan and Jimmy Asiku as also was the candidate most preferred by young voters. Young voters tend to vote for candidate who actively provide information of social media . To Maximize: Using Political media as channels of political communication should consider the frequency and actively. Abstrak Media sosial adalah salah satu media baru yang saat ini menjadi saluran informasi yang sering di gunakan pada masa ini. Tekhnologi berkembang mempermudah penggunaan media ini. Media sosial digunakan sebagai media komunikasi di berbagai bidang termasuk bidang politik. Kota manado adalah kota berkembang yang mengunakan saluran komunikasi ini di bidang politik pada pemilihan walikota dan wakil walikota Manado 2016. Setiap pasangan calon memberikan informasi lewat media sosial dengan harapan mendapatkan dukungan dan simpati. Penelitian ini mengunakan metode kuantitatif deskriptif. Teori yang digunakan teori media baru dan teori stimulus organisme respon (SOR). Hasil penelitian menunjukkan bahwa pemilih pemula aktif mengunakan media sosial dan menjadikan media sosial sebagai sumber informasi utama. Pasangan Harley Mangindaan adalah pasangan yang paling aktif memberikan pesan politik lewat media sosial dan juga pasangan yang paling banyak di pilih oleh pemilih pemula. Pemilih pemula cenderung memilih pasangan yang aktif memberikan informasi lewat media sosial kepada mereka.